Study of Adhesion Molecules in Diabetes Mellitus Type2 Iraqi Patients with Dyslipidemia - Alsaedy, Abbas M.; Al-Rubaei, Zeinab M. (Journal of the Faculty of Medicine Baghdad, 2024)
Background: Cell adhesion molecules are protein entities that are located on the cell surface. The vascular cell adhesion molecule-1 (VCAM-1) and intercellular adhesion molecule-1 (ICAM-1) expression is related to type 2 diabetes mellitus (T2DM) with dyslipidemia. Objectives: To determine the levels of VCAM-1 and ICAM-1 in T2DM patients with dyslipidemia and to explore the relationship between VCAM-1 and ICAM-1 and the development of dyslipidemia in T2DM patients.Patients and methods: The study included 150 individuals with an age range of (35-55) years. Patients with diabetes for more than 5 years were excluded. Fifty healthy individuals constituted Group 1 (G1), fifty patients with T2DM constituted Group 2 (G2), and fifty T2DM patients with dyslipidemia constituted Group 3 (G3). Whole blood samples were drawn to measure HbA1c based on fluorescence immunoassay technology. The serum was separated to measure fasting blood glucose (FBG), triglycerides (TG), total cholesterol (TC), and high-density lipoproteins (HDL) by manual methods, while VCAM-1, and ICAM-1 were determined using the ELISA test. The study was conducted between November 2022 and April 2023 at the National Center for Diabetes Treatment and Research, Baghdad, Iraq.Results: Significantly higher levels of FSG and HbA1c were detected in G2 and G3 compared to G1, but non-significantly so when G3 was compared to G2. Significant higher levels of TG and TC levels were detected for G3 when compared to G1 and G2, but non-significantly so when G2 was compared to G1. HDL levels were significantly lower in G3 compared to G2 and G1, but non-significantly so when G2 was compared to G1. VCAM-1, and ICAM-1 were significantly higher in G2 compared to G1, and VCAM-1 level was significantly higher in G3 compared to G2. Non-significant differences in ICAM-1 levels were found between G3 and G2.Conclusion: VCAM-1 and ICAM-1 are potentially significant factors in the development of dyslipidemia in diabetes patients. They might serve as biomarkers to accurately predict the progression of cardiovascular disease.